Teachers’ learning experiences while teaching refugees in Greece: ”it’s pretty extreme” - Jansen, Frederike (Adult Education Discourses, 2023)
Current global events lead to a sharp rise in the number of displaced persons. Since 2014, large new flows of refugees have been arriving in Europe and especially Greece, which has been the country through which many people on the move enter Europe (Koehler et al., 2018). Within refugee education, the role of teachers is acknowledged as critical facilitators of education (Bengtsson et al., 2020). Yet, few studies centre on teachers and their experiences while teaching. This paper explores how eight teachers describe their experience teaching in refugee education on the Greek islands and mainland and what they have learned from this life experience. Data was collected through interviews applying the biographical method inspired by Peter Alheit (1995; 2018). Within the analysis of teachers’ narratives, there was a focus on challenges and teaching strategies they created in response to the challenges, as well as the teachers’ ideas on the importance of education and variations in their stories due to working in different locations and teaching various age and gender groups. The learning experiences are contextualised with the concepts of transformative learning, habits of mind and points of view, connected to the Transformative Learning Theory by Jack Mezirow (1997; 2000; 2018). The challenges and strategies which emerged in teachers’ experiences are discussed with the findings of previous studies on education in refugee contexts.